Wetenskap op weg na 'n nuwe identiteit en samewerking - Plessis, P. G. W. du (Koers, 1994)
A traditional approach in Calvinist philosophy is to start with an analysis of cosmic diversity in order to find the identity of a particular phenomenon, and then to end with an account of the inter-relatedness between the phenomenon and other things. Although Stoker's philosophy tries to keep a balance between diversity and coherence as an entrée to reality - his later publications reflected a remarkable shift hy emphasising the coherence and contextual meaning of things. Taking the coherence and contextual meaning of things as the point of departure, this article explores a converse version of the traditional approach by using coherence (and not identity) as a means to sound out some new meanings of science and scientific co-operation. An indication of transdisciplinary co-operation is rendered in terms of the preponderance of reality‘s call upon man to be known and cared for. The article ends with a few examples of unusual concepts that may serve as a revised index to identify world-friendly and humane scientific activities.